Dynamic Migration of Surface Fluorine Anions on Cobalt‐Based Materials to Achieve Enhanced Oxygen Evolution Catalysis - Chen, Pengzuo; Zhou, Tianpei; Wang, Sibo; Zhang, Nan; Tong, Yun; Ju, Huanxin; Chu, Wangsheng; Wu, Changzheng; Xie, Yi (Angewandte Chemie International Edition, 2018)
Fluorine‐anion surface engineering has now been used to activate catalytic active species, representing a completely new way of reconstruction toward oxygen evolution reaction (OER) active species. The electronegativity of the fluorine anion is the strongest so that it will be much easier to form weak metal–fluorine bonds with stronger ionicity, contributing to the dynamic migration of fluorine anions and finally enriching on the surface of both cobalt‐based oxide/oxyhydroxide. Surface enrichment of fluorine anions endows more hydrophilic surface character for accelerating the key process of oxygen‐related intermediate adsorption. Combining with an obviously improved electron transfer capacity, the F‐CoOOH/NF catalyst exhibits a greatly enhanced OER activity (270 mV at 10 mA cm−2) and reaction kinetics (54 mV dec−1) in alkaline medium. Surface anion engineering introduces a new concept for rational design advanced OER catalysts for energy conversion system. Surface engineering by using fluoride ions was used to activate the catalytically active species of Co‐based materials. This is a completely new way of reconstruction toward OER‐active species. OER=oxygen evolution reaction; F green, Co purple.